Speaking Challenges in Research Class of Non-English Student: A Case Study - Anggarini, Ida Fitri (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2024)
The challenge of speaking effectively can stem from various factors, both psychological and practical. This study delves into the speaking challenges encountered by non-English-speaking students enrolled in the research class at the Postgraduate Program of IAI Al Qolam Malang. This is necessary whereas postgraduate students must present their papers and seek for journal articles for research. By conducting a qualitatite case study, the research seeks to uncover a holistic understanding of these challenges, exploring their multifaceted nature and implications. The findings aim to provide a foundation for informed pedagogical approaches, fostering improved language skills and communication in diverse academic settings. This research contributes to the broader discourse on language education, intercultural communication, and the adaptability of teaching methodologies in international educational contexts.